(untitled) (Contemporary Central & East European Law, 1974)
The article tackles the problem of the changes in the polish labour law after Second World War related to the creation of new social and economic reality of Polish People’s Republic. The process of adapting the legislation to the new reality was complex and consisted both of introducing totally new legal acts and of modifying the existing legal acts. There were also conventions concluded with the trade unions. What is worth mentioning, the provisions of this conventions not only enriched the new legal system by adapting it to the special demands of certain sectors but were then progressively introduced to the whole legal system. The introduced changes aim was to eliminate the inequalities between employees (as, inter alia, regulation of the paid leaves). Before war it was differentiated accordingly to the character of work – it was a month for an intellectual employee and 8 days for physical workers. Equal rights were also introduced in other fields, as: dismissal without notice, the rights in case of illegal dismissal, the social insurance, pensions, incapacity benefits and the child care allowance. The multitude of different legal acts concerning important questions of labour law made it difficult to use it in practice. This lead to the need of the codification, which was finally adopted and entered into force on the 1st January 1975. This codification covered most of the issues, except social insurance which was regulated by legal acts from the 23rd January 1968. What is important the Labour Code was to be applied to every employee, disregard the type of their contract (for example to members of workers’ cooperatives, vocational training contract and other than contract types, as nomination, vocation and election). The regulation concerning public officers was restricted to specific professions as: railway and post workers, forest administration workers, teachers, justice administration employees and scientists. These acts were considered as lex specialis. What is important there is a need to differentiate between nomination and vocation, and the latter was extended in comparison to previous legislation. It concerned not only the directors of the enterprises and the employees of higher level but also chief accountants and local administration officers. The workers of the agricultural cooperatives, rest beyond the scope of the labour law, and were subject to the regulation of agricultural law. It is highlighted that the references to other legislative acts were introduced to the labour law codification. Thanks to these links, the similar norms were not multiplied in different legal acts, what helped to reduce the complexity of regulation. The provisions of these acts should be applied only if they are not contradictory to the labour law regulation, what is the realisation of the subsidiary character of this regulations. Meaningful is that the norms of the labour code are ius cogens and can be only changed, if the change is in favour to the employee.